A Systematic Review of Early Intervention for Suicide Prevention among College Students - Khadijah, Siti; Yusuf , Ah; Nihayati, Hanik Endang (International Journal of Psychosocial Rehabilitation, 2020)
Suicide is a worrying health problem with a high prevalence among students. An effective and efficient program in preventing suicide is needed for campus environments. This research investigated various forms of suicide prevention programs and identified the most effective and efficient interventions. The databases were Scopus, Proquest, Pubmed, Cinahl, and SagePub using keywords consisting of “intervention”, “suicide” and “college student”. This systematic review used Item Reporting Approach for Systematic Review and Meta-Analysis (PRISMA) to analyze 15 articles extracted from databases using specific criteria. The interventions to reduce the risk of suicide among student were peers’ willingness to intervene, positive thinking and social support, affirmation, spiritual motivation, web-based videos, online screening and counseling, online mental health assistance, surveys web-based personal experiences, Question-Persuade-Refer (QPR) training with Gatekeepers, dialectic group skills training and group cognitive therapy, and social norm campaigns. There are advantages and disadvantages of suicide interventions concerning student compliance, faculty staff involvement, a small number of subjects and social stigma about mental illness. Web-based or online interventions posed more advantages, especially about the social stigma. Web-based or online interventions were the most preferred interventions among students because they had a lower chance of creating a negative stigma.